2021
DOI: 10.1111/nph.17256
|View full text |Cite
|
Sign up to set email alerts
|

Altered plant carbon partitioning enhanced forest ecosystem carbon storage after 25 years of nitrogen additions

Abstract: Summary Decades of atmospheric nitrogen (N) deposition in the northeastern USA have enhanced this globally important forest carbon (C) sink by relieving N limitation. While many N fertilization experiments found increased forest C storage, the mechanisms driving this response at the ecosystem scale remain uncertain. Following the optimal allocation theory, augmented N availability may reduce belowground C investment by trees to roots and soil symbionts. To test this prediction and its implications on soil bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 103 publications
6
79
1
Order By: Relevance
“…Although many, perhaps most, studies were multifaceted in their scope, for brevity only the main focus and findings are summarized. All told, these studies comprise a sample period that extends from three years [39] to 30 years of treatment [12]. Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many, perhaps most, studies were multifaceted in their scope, for brevity only the main focus and findings are summarized. All told, these studies comprise a sample period that extends from three years [39] to 30 years of treatment [12]. Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…There was, however, a high degree of interspecific variability in such a response. Despite slower tree growth, excess N has led to greater storage of C in soil and vegetation [12]. Finally, there has been a pronounced shift in herb layer composition that arose from increases in a nitrophilic species, blackberry (Rubus allegheniensis Porter) (hereafter, Rubus) [55], that competitively eliminated numerous N-efficient herbaceous species, resulting in a loss of plant diversity [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the optimal allocation theory, plants would allocate more biomass towards organism acquiring the most limiting resources (McCarthy and Enquist 2007). For this study, enhanced N availability from N deposition reduced the plant dependence on root systems for absorbing nutrients and subsequently lowered belowground C investments to roots (Eastman et al 2021), allowing plants to invest more C towards acquiring other limiting resources. This altered biomass allocation strategy suggests that plant biomass allocation patterns under global changes are closely linked with resource availability.…”
Section: Sensitivity Of Aboveground Plant Biomass To Elevated Co 2 In the Alpine Meadowmentioning
confidence: 90%
“…While elevated O 3 levels and reactive nitrogen (N) deposition often co‐occurs (Feng, Shang, Li, et al, 2019; Zeng et al, 2019), there have been very few studies exploring the potential interactive effects of these two variables on rhizosphere microbial communities. N fertilisation can profoundly alter plant growth, physiology, and productivity, all of which may shape the associated soil microbial community (Eastman et al, 2021; Zhang et al, 2018). Prior studies of O 3 × N interactions have primarily focused on aboveground effects and have yielded contradictory results, with some authors having reported that N addition can reverse the negative impact of O 3 exposure (Handley & Grulke, 2008; Mills et al, 2016), whereas others observed the opposite effect (Azuchi et al, 2014; Brewster et al, 2018) or detected no relationship between these variables (Feng, Shang, Li, et al, 2019; Harmens et al, 2017; Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%